Un paseo por las artes visuales en la Colección Carlos Monsiváis catálogo de la exposición presentada en el Museo del Estanquillo del 22 de junio al 3 de noviembre de 2019 (Asociación Cultural El Estanquillo, A.C., 2020)
The exhibition catalogue presents pieces illustrating the considerations written by Monsiváis on the work of artists such as Angelina Beloff, Lola Álvarez Bravo, Julio Ruelas, Gerardo Murillo Dr. Atl,, Roberto Montenegro, Nahum B. Zenil, Vlady, José Luis Cuevas, Agustín Jiménez, Hugo Brehme, Olga Costa, Vicente Rojo, Francisco Toledo, Luis García Guerrero, Miguel Covarrubias, Graciela Iturbide, Julio Ruelas, Natalia Baquedano, José Chávez Morado, Roberto Montenegro and Leopoldo Méndez, among others. Curated by Miriam Kaiser, the exhibition consists of more than 400 pieces including photographs, drawings, prints and paintings by these modern and contemporary artists.